METODE PENDIDIKAN INTEGRATIF DALAM MEMBENTUK AKHLAK SISWA SEKOLAH DASAR - Jabar Idharudin, Abdul; Nurhasanah, Muwahidah; Samsuddin (As-Sulthan Journal of Education, 2025)
Westernization and the currents of globalization have facilitated the spread of educational liberalism, gradually eroding students’ faith and moral character as acts of immorality increasingly become perceived as part of societal culture. This growing concern over various forms of student social deviation underscores the importance of studying the implementation of educational methods in shaping the character of elementary school students, so that children can be guided early to develop noble morals and grow into a distinguished generation. Using a qualitative approach, this study collected data through observation, interviews, and documentation, and analyzed it using descriptive-interpretative techniques, with the research conducted at the Integrated Islamic Elementary School Al-Hidayah Bogor. The findings indicate that integrative educational methods function effectively and systematically when aligned with a supportive school system and environment, enabling learning activities and school programs to synergize in forming students’ character at school, at home, and within the community through five main methods: exemplary behavior (keteladanan), habituation, encouragement and deterrence (targhib and tarhib), storytelling, and reflection and contemplation (tafakkur and tadabbur).